An outbreak of Listeria monocytogenes meningitis in neonates - Maria Landgraf, Ilka (1999)
Listeria monocytogenes, a Gram-positive, nonsporeforming rod has been isolated from mammals, birds, fish, crustaceans, and insects, being the primary habitats, the soil and decaying vegetable matter. It causes infection in humans and domestic animals. In humans it occurs with the highest incidence in neonates and in individuals older than 60, being meningitis a common manifestation of listeriosis. From five neonates borne at the same Obsthetric Center of an hospital in Great São Paulo, L. monocytogenes was isolated from cerebrospinal fluid (CSF). AlI strains bellonged to the same serovar, L4b. The resistance to antibacterial agents was tested. The mothers of 6 neonates, one of which died before having the CSF obtained, had stool and urine collected. From these materiaIs the microorganism was not isolated.